Cerebral Hypoperfusion in Posterior Reversible Encephalopathy Syndrome is Different from Transient Ischemic Attack on CT Perfusion. Issue 4 (25th September 2014) - Vanacker, Peter; Matias, Gonçalo; Hagmann, Patric; Michel, Patrik
ABSTRACT BACKGROUND PRES is a reversible neurotoxic state presenting with headache, altered mental status, visual loss, and seizures. Delayed diagnosis can be avoided if radiological patterns could distinguish PRES from cerebral ischemia. METHODS Clinical and radiological data were collected on all hospitalized patients who had (1) discharge diagnosis of PRES and (2) acute CTP/CTA. Data were compared with 10 TIA patients with proven cytotoxic edema on MRI. RESULTS Of the four PRES patients found, three were correlated with acute blood pressure and one with chemotherapy. At the radiological level, quantitative analyses of the CTP parameters showed that 2 out of 4 patients had bilaterally reduced CBF‐values (23.2‐47.1 ml/100g/min) in occipital regions, as seen in the pathological regions of TIA patients (27.3 ± 13.5 ml/100g/min). When compared with TIA patients, the pathological ROI's demonstrated decreased CBV‐values (3.4‐5.6 ml/100g). Vasogenic edema on MRI FLAIR imaging was seen in only one PRES patient, and cytotoxic edema on DWI‐imaging was never found. CT angiography showed in one PRES patient a vasospasm‐like unilateral posterior cerebral artery. CONCLUSIONS If confirmed by other groups, CTP and CTA imaging in patients with acute visual loss and confusion may help to distinguish PRES from bi‐occipital ischemia. These radiological parameters may identify PRES patients at risk for additional tissue infarction.